Clinical Outcomes of Uniportal Versus Multiportal Endoscopic Thoracic Sympathectomy in Patients With Severe Palmar and Axillary Hyperhidrosis - Oktay Aslaner (Acta Medica Alanya)
Aim: Palmar and axillary hyperhidrosis is caused by overstimulation of the sympathetic nervous system that control the sweat glands. This study compares the clinical consequences of uniportal and multiportal thoracic endoscopic thoracic sympathectomy (ETS), in cases of severe palmar and axillary hyperhidrosis.Methods: In this retrospective study, forty-one patients who were diagnosed as severe palmar and axillary primary hyperhidrosis were analyzed. These underwent multiportal ETS between 2015 and 2020 at our thoracic surgery clinic. They were divided into two groups, 24 as uniportal (58.5%) and 17 as multiportal (41.5%). They were compared in terms of the length of hospital stay, the initial complications and possible recurrences after three months. Descriptive statistics were used to evaluate stratified and continuous variables.Results: There was no significant difference in moderate pain between the two groups. There was a significant difference between the two groups in terms of 3 days or more hospitalization. There were no significant difference related to the rate of complications such as ptosis, Horner syndrome, increased duration of surgery and recurrence rate of hyperhidrosis 3 months after surgery. Some mild to moderate side effects disappeared spontaneously at 6-month follow-up.Conclusion: The results showed that uniportal and multiportal endoscopic thoracoscopic sympathectomy (EST) are very effective, safe and minimally invasive methods for the treatment of palmar and axillary hyperhidrosis. Compared to the multiportal approach, uniportal EST causes less postoperative pain and less surgical duration.